Aggregation and redispersion of silver species on alumina and sulphated alumina supports for soot oxidation. Issue 16 (21st July 2017) - Gao, Yuxi; Wu, Xiaodong; Liu, Shuang; Ogura, Masaru; Liu, Minghan; Weng, Duan
Abstract : Ag particles anchored on sulfated alumina, while free particles aggregated during soot oxidation, followed by redispersion triggered by O2 . Abstract : Soot oxidation was conducted over Ag/Al2 O3 and Ag/SO4 2− /Al2 O3 catalysts. Spent catalysts were found to exhibit higher activities than fresh ones for soot oxidation in oxygen. Environmental transmission electron microscopy (ETEM) was performed for the catalytic oxidation of soot over fresh and spent catalysts. Aggregation of silver nanoparticles occurred significantly on the alumina support under very low oxygen pressure. On increasing the oxygen pressure, redispersion of large Ag particles was observed on both supports, which explains the superior activities of the spent catalysts. Sulphated alumina was found to anchor the silver species effectively and deter the migration of silver to soot particles. Hence, the aggregation of silver was alleviated over Ag/SO4 2− /Al2 O3, leading to higher activity than the Ag/Al2 O3 catalyst.